2009
DOI: 10.1177/0959683609104031
|View full text |Cite
|
Sign up to set email alerts
|

Holocene fire-related alluvial-fan deposition and climate in ponderosa pine and mixed-conifer forests, Sacramento Mountains, New Mexico, USA

Abstract: We employed 14C dating of alluvial-fan deposits in ponderosa pine and mixed-conifer forests of the Sacramento Mountains, New Mexico to document Holocene fires and related geomorphic impacts. Rapid aggradation by charcoal-rich debris flows occurred in the middle Holocene (5800—4200 cal. yr BP), indicating episodic sedimentation following severe fires. Fire-related deposition virtually ceased ~4200 cal. yr BP, with most fan deposits indicating slower aggradation with cumulic soil development until 1800 cal. yr B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…Alluvial fans -their process domains, sedimentology, stratigraphy, and models of development -have been researched in a variety of arctic-alpine, temperate, and tropical environments (e.g., Hooke, 1967;Bull, 1977;Boothroyd and Nummendal, 1978;Kesel and Spicer, 1985;Rachocki and Church, 1990;Catto, 1993;Blair and McPherson, 1994;Blair, 1999aBlair, , 1999bBlair, , 2001Anderson et al, 2000;Frechette and Meyer, 2009;Giles et al, 2010). It is widely recognised that fans may be predominantly fluvial or colluvial in origin and that the extent to which these different types of geomorphic activity dominate fan development may change over time.…”
Section: Introductionmentioning
confidence: 99%
“…Alluvial fans -their process domains, sedimentology, stratigraphy, and models of development -have been researched in a variety of arctic-alpine, temperate, and tropical environments (e.g., Hooke, 1967;Bull, 1977;Boothroyd and Nummendal, 1978;Kesel and Spicer, 1985;Rachocki and Church, 1990;Catto, 1993;Blair and McPherson, 1994;Blair, 1999aBlair, , 1999bBlair, , 2001Anderson et al, 2000;Frechette and Meyer, 2009;Giles et al, 2010). It is widely recognised that fans may be predominantly fluvial or colluvial in origin and that the extent to which these different types of geomorphic activity dominate fan development may change over time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tree-ring data suggest that regionally extensive droughts in the late 1200s and late 1500s CE caused increased tree mortality throughout the SW US (3). Additionally, recent sedimentary charcoal studies identified cases of unusually severe wildfire events (but of unknown extent) in some SW forests dating to the 1200s CE period, and during warm mid-Holocene periods (32). More recently, mortality of many SW tree species occurred during the severe drought of the 1950s (3,18).…”
Section: Extensive Tree Mortality Due To Fires and Bark Beetlesmentioning
confidence: 99%
“…Historical ecology studies of SW forests show extensive wildfires and bark-beetle infestations to be natural disturbance processes linked to climate variability (3,(31)(32)(33)(34). For example, tree-ring data suggest that regionally extensive droughts in the late 1200s and late 1500s CE caused increased tree mortality throughout the SW US (3).…”
Section: Extensive Tree Mortality Due To Fires and Bark Beetlesmentioning
confidence: 99%
“…Charcoal in fluvial sediments cannot be interpreted in this way, as both deposition rates and sediment textures may vary significantly. Despite these challenges, reconstructing fire history from these environments has advantages, in particular being able to directly connect the charcoal record to geomorphic responses to fire [32][33][34][35][104][105][106]. Streams and floodplains are also landscape systems that humans would have regularly used (and indeed often also contain archaeological materials).…”
Section: Approach and Research Rationalementioning
confidence: 99%